Application of Wireless Sensor Network and RFID Monitoring System in Airport Logistics - Le, Wang (International Journal of Online and Biomedical Engineering (iJOE), 2018)
To better regulate the airport cargo transportation, we presented the design of an airport logistics monitoring system based on WSN and RFID. The monitoring system is mainly composed of four modules: RFID system, wireless sensor monitoring network, communication network and remote monitoring terminal. Wireless sensors mainly include temperature sensors, humidity sensors and smoke sensors. The sensors can collect the environment data such as goods temperature, humidity and smoke and so on. The node sensor module is implemented in such a way that the sensor is connected to the node in a plug-in manner, that is, the sensors are integrated on a sensor panel and the sensor data is transferred through the standard I / O interface between the sensor panel and the node. The system can realize real-time tracking and positioning of airport cargo, collecting cargo information.